Uma aproximação à problemática do labirinto em alguns andamentos diacrónicos de inspiração helénica (de Ovidio a Pausânias e de Boccacio e Agricola a Valkenborch) - Cadafaz de Matos, Manuel (Amaltea. Revista de Mitocrítica, 2009)
Between the first and the XX centuries, the labyrinth had exerced a curious interest to a great number of European intellectuals, such as poets, like the Roman poet, Ovide (I century); the Hellenic thinker, Pausanias (II century); the Italian theorician of myths and writer, Giovanni Boccaccio (XIV century); or the Flemish erudite musical composer, Alexander Agricola (XV century). The author of this study, in a diachronic point of view, analyses also the contribution two Flemish painters in the XVI century, Lucas I van Valkenborch and Hans Bol, who, after suffering some years in the exile, has expressed, in their pictures, their feelings about the labyrinth and about the Daedale and Icare myths.